TELAAH ILMIAH INDUSTRI KEUANGAN NON-BANK (INBK) SYARIAH DAN EKSISTENSINYA DI INDONESIA PASCA COVID-19 - Sholiha, Imroatus (Al-Idarah, 2023)
The purpose of this study is to examine Islamic financial institutions that are included in the Islamic Non-Bank Financial Industry (IKNB) and how they exist in Indonesia after Covid-19. The institutions studied in this study are Islamic insurance, Islamic financing institutions, Islamic pension funds, Islamic special financial services institutions, Islamic micro institutions, and Islamic fintech. The research used literature, namely research by examining several literature related to the issues raised and then reported qualitatively descriptively. The results showed that when the Covid-19 pandemic hit, IKNB Syariah experienced a decline in performance in several sectors, but overall it was still able to survive and grow positively, as evidenced by an increase in assets in 2021 of 4.409 billion from the previous year. Post-covid-19 Sharia IKNB assets in March 2022 amounted to 126.236 billion, an increase in November of 143.971 billion. IKNB Syariah has shown its existence after Covid-19.